Der deutsche Leistungsbilanzüberschuss: Handelspolitische Anknüpfungspunkte unter dem Dach der WTO - Bastian Alm; Sebastian Weins (Wirtschaftsdienst, 2017)
Seit 2011 weist Deutschland ununterbrochen den weltweit höchsten Leistungsbilanzüberschuss auf. Eine Reihe von Ökonomen und Politikern aus dem In- und Ausland sowie internationale Institutionen und Organisationen fordern die Bundesregierung deshalb seit einigen Jahren dazu auf, Gegenmaßnahmen zu ergreifen. Im Fokus stehen dabei regelmäßig Handlungsempfehlungen zur Stärkung der öffentlichen und privaten Investitionen sowie des Reallohnwachstums in Deutschland. Da die Leistungsbilanzungleichgewichte längst ein globales Phänomen sind, wird hier ein multilateraler handelspolitischer Ansatz diskutiert. – – Persistent and significant current account imbalances are often seen as one of the greatest threats to the global economy and a catalyst for protectionist tendencies. Germany is often criticised for running a high surplus. However, economists disagree about whether and to what extent the German current-account surplus is excessive and which policy measures could help to rebalance the current account. The authors argue that the German current-account surplus is a global phenomenon and hence requires in addition to economic policies that could stimulate investment activity in Germany an internationally coordinated approach. Taking into account the specific circumstances of a country, the WTO could act as an institutional framework to deal with global imbalances. In particular the WTO's Trade Policy Review Mechanism could be further developed into a forum for coordinating members' trade policy and for agreeing on reciprocal measures among members. The concrete design could be based on other established international mechanisms, such as the European Semester.
Keywords: F13; F32; F40; 330